Interactive Contextual Learning Media: Development and Impact on English Language Learning in Junior Secondary School - Ade Suci Chairany Sirait; R Mursid; Farihah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study aims to develop and evaluate an Interactive Contextual Learning Media (ICLM) to improve English reading comprehension among Grade VIII students, particularly in understanding procedure texts. The research problem originates from the recurring challenges in junior secondary English classrooms, including low student motivation, limited engagement, and the lack of contextual and interactive learning resources. Employing the Research and Development design with the ADDIE model, the study involved analysis, design, development, implementation, and evaluation stages. Expert validations were conducted by material, media, and instructional design specialists, while feasibility, practicality, and effectiveness were assessed through individual try-outs, small-group trials, and field testing. Data were collected using questionnaires, observations, interviews, and pretest–posttest assessments, and analyzed using descriptive statistics and independent t-tests. The findings indicate that the developed media achieved high feasibility ratings from experts (mean scores ranging from 4.32 to 4.79), and strong practicality responses from teachers (95%) and students (96%). In terms of effectiveness, students in the experimental class showed a significant improvement in learning outcomes, increasing from a mean pretest score of 62.30 to 85.93 in the posttest, while the control class showed no meaningful improvement. Statistical testing confirmed a significant difference between the two groups (p < 0.001), indicating that the ICLM had a substantial positive impact on students’ reading comprehension. Overall, the results affirm that integrating interactivity and contextual learning into digital media can effectively enhance students’ understanding of English texts and support more engaging and meaningful learning experiences in junior secondary education.